2012
DOI: 10.4161/auto.19738
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy is active in normal colon mucosa

Abstract: Recently, autophagy has been found to be strongly activated in colon cancer cells, but few studies have addressed the normal colon mucosa. The aim of this study was to characterize autophagy in normal human intestinal cells. We used the expression of LC3-II and BECN1 as well as SQSTM1 as markers of autophagy activity. Using the normal human intestinal epithelial crypt (HIEC) cell experimental model, we found that autophagy was much more active in undifferentiated cells than in differentiated cells. In the norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
39
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 54 publications
(84 reference statements)
6
39
0
1
Order By: Relevance
“…A recent study showed that both BECN1 over- and under-expression could be related to poor colon cancer prognosis, illustrating the multifunctionality of BECN1 and autophagy in cancer aggressiveness [34, 35]. Our results confirmed the inhibitory role of autophagy in CRC development, consistent with other reports of BECN1-mediated tumor progression inhibition.…”
Section: Discussionsupporting
confidence: 91%
“…A recent study showed that both BECN1 over- and under-expression could be related to poor colon cancer prognosis, illustrating the multifunctionality of BECN1 and autophagy in cancer aggressiveness [34, 35]. Our results confirmed the inhibitory role of autophagy in CRC development, consistent with other reports of BECN1-mediated tumor progression inhibition.…”
Section: Discussionsupporting
confidence: 91%
“…p62 is highly expressed in breast, lung, gastric, colon, esophageal, and hepatocellular carcinomas and is associated with poor cancer patient prognosis 3-6. In contrast, a recent study reported that p62 was downregulated in colon carcinomas 7. The aim of our study was to confirm whether p62 expression is altered in gastric and colorectal cancers and to address whether it is altered in other cancers.…”
mentioning
confidence: 87%
“…Autophagy refers to the engulfment and processing of cellular proteins, including damaged organelles and long-lived and misfolded proteins. Autophagy has been shown to be active in the normal colonic intestinal mucosa, more so in the proliferative component of colonic crypts (7), and has been suggested to play a role in intestinal cell survival during physiological stress (8). Among intestinal diseases, autophagy was first linked to pathogenesis of Crohn disease when genome-wide association studies identified mutations in the autophagy-related genes ATG16L1 and IRGM as risk factors for Crohn disease (9 -11).…”
mentioning
confidence: 99%